2018
DOI: 10.5505/agri.2018.10437
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Nursing Students About Pain Management

Abstract: The purpose of the present study was to examine the knowledge and attitudes of Turkish nursing students about pain management. Methods: The participants in this cross-sectional study were 190 nursing students who were studying at a nursing faculty in western Turkey. The research data were collected between March and June of the academic year 2015-2016, using a Student Description Form and the Nurses' Knowledge and Attitudes Survey Regarding Pain (NKASRP). Results: The mean age of the students in the study samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Moreover, the current study agreed with Al-Khawaldeh, et al ( 2013) who said that students demonstrated a poor understanding of pain knowledge and attitudes with a KASRP score of 34.1% (SD = 9.9) [15], and consistent with Alsaqri (2018) who found that nursing students have a lack of knowledge and attitudes towards pain management and the mean correct score for the entire scale was 41.8% (SD = 3.71) [16]. Furthermore, the current study is consistent with the results of Karman, et al ( 2018) who stated that the mean score of the NKASRP was 15.85 ± 3.25% (poor level of pain knowledge and attitude) [17]. And similar to the result of study conduct by Hroch (2017) who found that the mean score of the NKASRP was 66.7% and the major areas of weakness in pain knowledge and attitudes were related to understanding populations at risk of respiratory depression after receiving an opioid, dosage calculations, medication administration and pharmacology [18].…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the current study agreed with Al-Khawaldeh, et al ( 2013) who said that students demonstrated a poor understanding of pain knowledge and attitudes with a KASRP score of 34.1% (SD = 9.9) [15], and consistent with Alsaqri (2018) who found that nursing students have a lack of knowledge and attitudes towards pain management and the mean correct score for the entire scale was 41.8% (SD = 3.71) [16]. Furthermore, the current study is consistent with the results of Karman, et al ( 2018) who stated that the mean score of the NKASRP was 15.85 ± 3.25% (poor level of pain knowledge and attitude) [17]. And similar to the result of study conduct by Hroch (2017) who found that the mean score of the NKASRP was 66.7% and the major areas of weakness in pain knowledge and attitudes were related to understanding populations at risk of respiratory depression after receiving an opioid, dosage calculations, medication administration and pharmacology [18].…”
Section: Resultssupporting
confidence: 91%
“…This shows that the students had inadequate knowledge and inappropriate attitudes about pain and its management, which is consistent with the literature. [11][12][13]34,35 In the current study, the nursing students were found to have enhanced knowledge and attitudes just after the education (76.80%) and at 3 months after the education (65.91%) compared to their knowledge and attitudes before the education (45.85%). The lower score for knowledge and attitudes at 3 months after the education compared to the score just after the education suggests the effect of education on knowledge and attitudes.…”
Section: Knowledge and Attitudesmentioning
confidence: 48%
“…It was emphasized that pain management should be dealt with more extensively in the nursing curriculum. 12 Results of the studies suggest that nursing education about pain management needs to be improved. [9][10][11][12][13] Nurse educators are responsible for preparing nursing students for pain management before they start to work as a nurse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study assessed the level of knowledge and attitudes towards pain of final-year nursing students, which proved to be inadequate according to the minimum score set by the authors. Considering the overall mean KASRP score (55.8%), our population scored higher than other students in Saudi Arabia (42.6%), Turkey (40.64% and 45.85%), Jordan (34.1%), Iran (37%), and Egypt ( < 50%) ( Al-Khawaldeh et al, 2013 ; Erol Ursava ¸s & Karayurt, 2020 ; Gadallah et al, 2017 ;Karaman et al, 2018 ;Rahimi-Madiseh et al, 2010 ;Shdaifat et al, 2020 ), and lower than other studies conducted in Canada ( > 60%) and the USA ( > 70%) ( Duke et al, 2013 ;Hroch et al, 2019 ).…”
Section: Discussionmentioning
confidence: 66%